Unobserved Delegation - Chaim Fershtman; Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
The paper describes situations where commitment via delegation is beneficial, even when the delegation is unobservable and the players have the option to play the game themselves. The potentiual for such benefits depends on the type of delegation, incentive versus instructive, the possibility of repetition, and the probability of observability.
Keywords: 330